Diplomasi PT. Garuda Indonesia (Persero) Dalam Mendukung Pariwisata Melalui Program Wonderful Indonesia 2017-2021 - Solafide, Ratna Cempaka; Purwanto, Adi Joko (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2023)
Tourism is one of the most important sectors in increasing national economic growth. Foreign exchange from the tourism sector penetrated US 19.29 billion (2018), while the contribution to GDP reached 4.50% (2018) and 4.80% (2019). Of course, this achievement involves stakeholders including PT Garuda Indonesia Persero (Tbk), so it is appropriate to increase the interests of Indonesia through the tourism sector. So, the formulation of the problem in the research This thesis is: why and how the diplomacy of PT. Garuda Indonesia (Persero) in supporting tourism through the wonderful Indonesia program 2017-2021? The purpose of this study was to identify and describe (1) the reasons for PT. Garuda Indonesia (Persero) to support tourism through wonderful Indonesia 2017-2021, as well as (2) an overview of the diplomacy of PT. Garuda Indonesia (Persero) in supporting tourism through the wonderful.. program Indonesia 2017-2021. Meanwhile, this type of research is library research (library research) compiled with a qualitative approach so that the process research by collecting document data (reports, information from media, excerpts from books, journals, and other documents). With technique documentation, data analysis used in this research is descriptive qualitative. The results of this study, first; reason PT. Garuda Indonesia (Persero) support Indonesian tourism through the Wonderful Indonesia 2017- 2021, namely: (1) carrying out the roles and functions as Government stakeholders in the aviation and tourism sector with a profit-oriented business as well as a positive impact on the Indonesian economy; (2) support achievement national interest through the tourism sector. Apart from increasing access transportation, Garuda Indonesia must also contribute to building a positive image that good, which will later form good public opinion against Indonesia. Garuda Indonesia is also required to be able to reflect that Indonesia is a safe, peaceful, democratic country with diversity society and its cultural wealth. Second; diplomacy of PT. Garuda Indonesia (Persero) in supporting tourism through the Wonderful Program Indonesia 2017-2021 is implemented in two ways: (1) joining with alliance of airlines in the world (SkyTeam), take action Quantum Leap (safety, systems, facilities and human resources), and strengthen the image of Garuda Indonesia in the international market, (2) improve quality and service, namely by carry out its main vision as a leading airline company, competitive at the Asian level and experiencing sustainable growth (sustainable grow)â€, opening new flight destinations as an effort support the 10 Priority Tourism Destinations (DPP) (10 New Bali) programs as well as 5 Super Priority Tourism Destinations in Indonesia.